The Applicability of mediation in the resolution of criminal disputes in Kenya: a case for restorative justice in the criminal justice system - Mugo, Alice Kahithe (Strathmore University, 2017)
The purpose of carrying out this study is to discover whether mediation can be applied in the resolution of criminal disputes in Kenya and specifically, to find out at what point of the trial process criminal cases can be referred to mediation; whether mediation by itself, is sufficient for the resolution of criminal disputes; and the contribution that mediation can make to the offender’s rehabilitation. The research methodology for this study entails the use of journals and other secondary sources from Strathmore University’s online library resources, and international legal instruments. This study begins with the research proposal under which the problem, the research questions, and the purpose of the study are introduced. Chapter 2 deals with the theoretical framework, consisting of three interrelated theories, and the views of different authors are encompassed under the literature review. Chapter 3 entails a critical interrogation into the applicability of mediation in criminal cases. Chapter 4 is an examination of the international legal framework in place to deal with mediation of criminal matters. The last chapter contains a summary of the main findings of this study, in addition to the conclusion and recommendations. The main findings of this study are the following: mediation can be used to resolve criminal disputes; mediation can be introduced prior to the presentation of the case before court, after a guilty verdict but before sentencing, or after sentencing; and mediation can lead to a positive outcome for the case and a positive change on the offender’s behaviour. The major recommendations of this study are that mediation should be applied in Kenya in the resolution of criminal cases and that a legislation on criminal mediation would be necessary and would have to address three key areas- the conditions of referral of cases to mediation; the training and qualifications of mediators; and the outcome of cases after mediation.
Submitted in partial fulfillment of the requirements of the Bachelor of Laws Degree at Strathmore University Law School
Keywords: Criminal disputes; Mediation; Criminal cases